Financial Management Strategy of Medicall Clinic in Tegal City to Improve Profitability - Noor Roziq Ghulam Perdana; Arlette Suzy Puspa Pertiwi; Mira Veranita; Purwadhi Purwadhi (Jurnal Multidisiplin Sahombu, 2026)
This study aims to analyze the financial management strategy at the Tegal City Medicall Clinic as an effort to increase profitability. The research method used is descriptive qualitative through in-depth interview, observation, and documentation techniques, which are then analyzed with the stages of data reduction, data presentation, and conclusion drawn. The results of the study show that the financial management of the Medicall Clinic is still running simply without the support of detailed budget formal documents, is more reactive, and relies on predictions of stable routine needs, especially from BPJS Kesehatan cooperation revenue. The main obstacles include fluctuations in income from independent BPJS participants, time-consuming manual financial recording, and incomplete data due to some of the owner's personal funds not being recorded. The strategy of increasing profitability is carried out through improving service quality, expanding patient segments through direct marketing and home care service development, operational cost efficiency, and efforts to separate personal and clinical finances